Burned-out metastatic testicular tumor: Choriocarcinoma - El-Sharkawy, Mohammed S.; Al-Jibali, Abdulaziz S. (International Journal of Health Sciences, 2017)
Burned-out testicular tumor is a very rare clinical entity. There is no clinical finding in the testicle because it regresses spontaneously without any treatment and generally presents with metastases. Clinical examination of the testis and scrotal sonography are pivotal in the initial diagnosis of such neoplasms. We present a case of a 22-year-old male with hemoptysis, weight loss, and abdominal pain for the past 2 weeks and no palpable lesion on testicular examination. No relevant past medical history.